ANALISIS YURIDIS PELANGGARAN HAK CIPTA MENJUAL VCD LAGU BAJAKAN (STUDI KASUS PUTUSAN MA No. 2755 K/PID. SUS/2015) - Ferry Hermanto, Tri Reni Novita (NERACA KEADILAN, 2024)
Songs are part of copyright In Indonesia, which is protected by law, namely Law no. 28 of 2014 concerning copyright. One of the copyright violations that often occurs is the sale of pirated VCDs of songs. This research was conducted with the aim of finding out whether legal protection for creations in Indonesia has been properly and correctly enforced in accordance with the law and the purpose of the law and fulfills the rights of creators of creations. Data collection was carried out by means of library research. Literature research is by referring to primary, secondary and tertiary legal materials. In this case, it is in the form of laws, books, journals, articles and decisions taken from the supreme court website. To analyze the data, a qualitative approach was used, namely by analyzing the data in depth and then interpreting it which is expected to be able to answer the legal problems raised in this writing. The research results show that law enforcement has been carried out correctly but there are weaknesses that cause copyright violations to still occur in Indonesia. Therefore, it is necessary to update the law, strengthen institutions related to copyright, as well as disseminate information about copyright to the public, including in the realm of education.